Analisis Faktor Risiko Kejadian Preeklampsia Berat Di Rsud Rujukan Kabupaten Dan Provinsi Kalimantan Tengah - Legawati Legawati; Nang Randu Utama (Jurnal Surya Medika (JSM), 2017)
The maternal mortality rate (MMR) and infant mortality rate (IMR) is a barometer of a country's health services. In developed countries, the incidence of severe preeclampsia and eclampsia ranges from 6-7% 0.1 to 0.7%. While the maternal mortality rate due to pre-eclampsia and eclampsia in developing countries is still high (Betty & Yanti, 2011). To analyze the risk factors of weight in Pre eclampsia Referral Hospital Sultan Imanudin Pangkalan Bun and Dr. Doris Sylvanus Palangkaraya. This was an observational study conducted using a cross sectional study design. A cross-sectional study is when the influence of independent variables (exposure) and the dependent variable (effect) is observed and measured at the same time. Based on multivariable logistic regression analysis of factors affecting the risk factors PEB is the mother's age, education, gestational age, parity, ANC. Factors unrelated significantly is work, spacing, PE history, history of diabetes, Gemelli, economic and social decision-making. Factors that increase the risk of PEB is the mother's age, education, occupation, gestational age, parity, history of PE, the ANC and the social economy. Factors unrelated significantly is spasing, history of diabetes, Gemelli, and decision making. For pregnant women can do a pregnancy without looking at risk factors for PEB or no risk factors, to see some of the risk factors determinants. For health workers to carry out pregnancy tests with a focus on the pregnancy.